Adult-onset Still’s disease: A disease at the crossroad of innate immunity and autoimmunity - Rao, Shijia; Tsang, Lemuel Shui-Lun; Zhao, Ming; Shi, Wei; Lu, Qianjin (Frontiers in Medicine, 2022)
Adult-onset Still’s disease (AOSD) is a rare disease affecting multiple systems and organs with unknown etiology, and the clinical symptoms are usually described as spiking fever, arthritis, evanescent salmon-pink eruptions, lymphadenopathy, splenomegaly, and other manifestations. The laboratory indicators are not specific, often presenting as increased leukocyte counts and neutrophil percentage, elevated erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), hyperferritinemia, and increased inflammatory factors. ANA, ENA, and RF are negative. According to those unspecific clinical presentations and laboratory findings, infection, tumor, connective tissue disease, and other diseases must be ruled out before diagnosis. The diagnosis of AOSD is a great challenge for clinicians. The mechanism of AOSD pathogenesis is complicated and still being studied. There is a new opinion that atypical persistent skin eruptions (APSEs) with specific histological manifestations are unique for AOSD, and APSEs might be on a spectrum with classical evanescent eruptions. Studies on APSEs showed that IL-1β and IFN-γ are strongly correlated with the pathogenesis of necrosis keratinocytes in APSEs. IL-1β is strongly involved in inflammatory disease when it is abnormal, and plays an important role in the pathogenesis of neutrophil dermatosis. In the early stage of AOSD, skin lesions appear to be evanescent urticaria-like eruptions accompanied by fever, and only neutrophils infiltrate around the blood vessels in the dermis pathologically. As the course of the disease progresses, IL-1β is gradually released. Through the stimulation of other inflammatory factors and the influence of unknown factors, IL-1β gradually infiltrates into the stratum corneum and finally accumulates around the necrotic keratinocytes of the stratum corneum. However, the detailed mechanism is still unknown. IFN-γ could play a pro-inflammatory or regulatory role in some disorders. IL-1β can enhance the expression of IFN-γ, and IFN-γ can cause keratinocyte apoptosis by activating the autocrine of caspase. Also, several pieces of evidence indicate that adaptive immunity is also involved in the pathogenesis of AOSD. Increased α-soluble receptors of IL-2 may suggest T-cell activation and proliferation in AOSD patients. Increased IL-4- and IFN-γ-producing T cells were found in active AOSD and related to disease severity. Frequencies of Treg cells in AOSD were significantly lower and were inversely correlated with disease severity. According to these, more and more researchers have reached a consensus that AOSD is a disease at the crossroads of innate immunity and autoimmunity. In this review, we will provide a comprehensive insight into AOSD, describing research progress and the immunological mechanism contribution to the disease. In the meantime, different treatment options and the efficacy and safety of various biologic agents are also discussed. A further understanding of AOSD requires closer cooperation among doctors from different departments, and this review will provide a new idea for diagnosis and therapeutic options.